Heat transfer analysis of arrhenius-controlled free convective hydromagnetic flow with heat generation/absorption effect in a micro-channel - Godwin Ojemeri; Muhammed M. Hamza (Alexandria Engineering Journal, 2022)
The study of a chemically reacting fluid in a vertical micro-channel limited to an applied transverse magnetic field that has fully developed steady natural convection flow under the impact of internal heat generation or absorption effects is the focus of this research. The governing equations are solved in dimensionless form using the homotopy perturbation method, HPM. Temperature, velocity, volume flow rate, and frictional drag force fundamental flow attributes are investigated as a function of controlling parameters such as heat generating or absorbing parameters, chemical reaction parameter, rarefaction parameter, fluid-wall interaction parameter and wall-ambient temperature difference ratio. The results are thoroughly analyzed and graphically depicted in a variety of plots. It is worth noting that raising the chemical reaction and rarefaction parameters increases fluid flow and volume flow rate, respectively. Furthermore, the action of heat absorption is observed to suppress fluid flow whereas heat generation establishes the opposite condition. Additionally, numerical data was generated and tabulated to compare the findings of this study to those of Jha et al. (2014) when the chemical reactant and heat generating/absorbing parameters were neglected, and an excellent agreement was discovered.